A 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells and its preparation method and application

Through 3D printing technology combining nanobeta-tricalcium phosphate with micron-level concave and concave and convex rod soil, porous bone defect repair scaffolds were prepared, which solved the problem of insufficient biological activity and bone induction performance of bone defect repair materials in the prior art, and achieved bone marrow Effective adhesion and differentiation of mesenchymal stem cells significantly improve the bone repair effect.

CN117045859BActive Publication Date: 2024-12-24SHENZHEN UNIV GENERAL HOSPITAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311209816.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2024-12-24
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

The biological activity and osteoinduction performance of existing bone defect repair materials are poor, and it is difficult to effectively promote the adhesion, proliferation and differentiation of bone marrow mesenchymal stem cells, resulting in poor bone repair results.

Method used

Using 3D printing technology that combines nanobeta-tricalcium phosphate with micron-level concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and conca , enhance the osteoinductive biological activity of the material.

Benefits of technology

It improves the biological performance of bone defect repair scaffolds, promotes the adhesion, migration and differentiation of bone marrow mesenchymal stem cells, enhances bone formation, and achieves excellent physical and biological performance of bone repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117045859B_ABST
    Figure CN117045859B_ABST
Patent Text Reader

Abstract

The present invention discloses a 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells and its preparation method and application, belonging to the field of biomaterial technology. The method steps of the present invention are as follows: (1) adding nano β-tricalcium phosphate or nano β-tricalcium phosphate and micron-grade attapulgite to a pre-mixed photosensitive resin system, mixing the obtained mixed slurry, 3D printing light curing molding after light-proof degassing treatment, obtaining a porous scaffold, washing, drying, degreasing and sintering; (2) sterilizing the porous scaffold after degreasing and sintering, and then inoculating the BMSCs suspension on the porous scaffold, using H-DMEM culture medium containing 10% FBS to culture for 1-2 weeks and then taking it out, and freeze-drying it after decellularization. The porous scaffold structure prepared by the present invention can stimulate BMSCs to secrete bone regeneration-related growth factors and adsorb them in attapulgite, play a loading and protective role, enhance the bone-inducing biological activity of the material, accelerate the formation of bone, and is expected to be used as a bone repair material with excellent biological properties for the biomedical field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomaterials, and specifically relates to a 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells, and a preparation method and application thereof. Background Art

[0002] Bone defect refers to the loss of part of the bone tissue due to trauma, infection, tumor or other diseases. In healthy people, when a small bone defect occurs in the bone, the bone tissue can heal naturally. When the range of bone tissue loss reaches the critical bone defect length, it exceeds the ability of the bone tissue to repair itself, and surgical intervention is required to repair this section of defective bone tissue. In bone tissue engineering technology, scaffold materials, seed cells, and growth factors are the three important elements. Seed cells are the main force in bone defect repair. Commonly used seed cells include embryonic stem cells, amniotic membrane stem cells, umbilical cord blood stem cells, bone marrow mesenchymal stem cells, etc. They all have the potential for multidirectional differentiation, but existing studies have shown that bone marrow mesenchymal stem cells (BMSCs) have the advantages of a wider source, easier material collection, and no immune rejection reaction with patients. In the future, they may become the best choice for the treatment of orthopedic diseases. Scaffold materials are three-dimensional frameworks for seed cells to attach, grow and differentiate. Through interaction with the body system, they can directly affect the repair process and effect of bone tissue defects.

[0003] Existing research results show that the porosity and pore size of scaffold materials play an important role in bone formation. When the porosity of the scaffold material is 60% to 80%, it is an ideal state. It can not only regulate the speed of its own degradation, but also promote the adhesion, proliferation and differentiation of seed cells. The macroporous structure of the scaffold material (pores between 100 and 800 μm) is conducive to the formation of blood vessels and new bones, the microporous structure (pore size between 10 and 100 μm) is conducive to cell growth, and the microporous structure (pore size below 10 μm) is conducive to the penetration of liquids.

[0004] Attapulgite (ATT) is a clay mineral, the main component of which is palygorskite or trochosite. It is a magnesium-rich silicate with a 2:1 type layered chain crystal porous structure. Due to its unique microstructure and properties, it has many excellent properties, such as adsorption, adhesion, catalysis, etc., and is widely used in the fields of food, chemical industry and biomedicine. However, there are few studies on the application of attapulgite to 3D printing bone defect repair scaffolds in the prior art.

[0005] Based on the above reasons, this application is filed. Summary of the invention

[0006] Based on the above reasons, in view of the problems or defects existing in the prior art, the purpose of the present invention is to provide a 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells and a preparation method and application thereof, so as to solve or at least partially solve the above technical defects existing in the prior art: the present invention can solve the technical problem of poor biological activity and bone induction performance of existing bone defect repair materials.

[0007] The first aspect of the present invention provides a method for preparing a 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells, comprising the following steps:

[0008] (1) adding nano-β-tricalcium phosphate or nano-β-tricalcium phosphate and micron-grade attapulgite to a pre-mixed photosensitive resin system according to a ratio, mixing the obtained mixed slurry, degassing it in a dark place, and then performing 3D printing and photocuring to obtain a porous scaffold, washing, drying, degreasing and sintering;

[0009] (2) The porous scaffold after degreasing and sintering in step (1) is disinfected, and then a bone marrow mesenchymal stem cell suspension is inoculated on the porous scaffold at a certain concentration, cultured in H-DMEM medium containing 10% FBS for 1-2 weeks, taken out, decellularized and freeze-dried to obtain the 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells.

[0010] Furthermore, in the above technical solution, the size of the micron-sized attapulgite in step (1) is 15-30 μm.

[0011] Furthermore, in the above technical solution, the mixed slurry in step (1) preferably includes nano-β-tricalcium phosphate and micron-sized attapulgite.

[0012] Furthermore, in the above technical solution, the mass ratio of the nano-β-tricalcium phosphate and the micron-sized attapulgite in step (1) is 95-105:1.

[0013] Furthermore, in the above technical solution, the photosensitive resin system in step (1) includes a photosensitive resin, a photoinitiator and a dispersant.

[0014] Furthermore, in the above technical solution, the photosensitive resin is one or more of 1,6-hexanediol diacrylate (HDDA), trimethylolpropane triacrylate (TMPTA) and Di-TMPTA.

[0015] Furthermore, in the above technical solution, the photoinitiator is TPO or TPO-L.

[0016] Furthermore, in the above technical solution, the dispersant is one or more of BYK-103, BYK-110, OA or ammonium polyacrylate.

[0017] Furthermore, in the above technical solution, in step (1), in a preferred embodiment of the present invention, the mixing method of the mixed slurry is ball milling, and the ball milling mixing is specifically to prepare zirconium oxide balls according to a certain grade, and then mix the mixed slurry with zirconium balls, and then screen out the ball milling beads after ball milling.

[0018] Furthermore, in the above technical solution, in a preferred embodiment of the present invention, the ball-to-material ratio of the zirconium balls to the mixed slurry is 2:1.

[0019] Furthermore, in the above technical solution, the ball milling speed is 100-500 rad / min, and the ball milling time is 5-15 h; in a preferred embodiment of the present invention, the ball milling speed is 300 rad / min, and in a preferred embodiment of the present invention, the ball milling time is 12 h.

[0020] Furthermore, in the above technical solution, the solid content of the mixed slurry in step (1) is 30 vol% to 40 vol%.

[0021] Furthermore, in the above technical solution, the specific process of degreasing and sintering in step (1) is as follows: first keep the temperature at 300-600°C for 30-60 minutes, then heat to 1000-1500°C and keep the temperature for 90-180 minutes.

[0022] Furthermore, in the above technical solution, the heating rate used in the degreasing sintering is 0.5-2°C / min.

[0023] Furthermore, in the above technical solution, the concentration of the BMSCs cell suspension in step (2) is 1 to 2*10 6 / ml.

[0024] The roles played by the raw materials used in the present invention are as follows:

[0025] The nano β-tricalcium phosphate used in the present invention contains calcium and phosphorus elements, is a bone active material, and can play a role in inducing bone regeneration; moreover, the nano β-tricalcium phosphate used in the present invention is weakly alkaline, can neutralize the pH value of the lesion, and the degraded calcium ions can be used as raw materials for bone formation; the nano β-tricalcium phosphate can also stimulate BMSCs cells to secrete bone regeneration-related factors such as BMP2.

[0026] The porous structure of the attapulgite used in the present invention can absorb the bone regeneration-related factors secreted by BMSCs cells, play a slow release role, and continuously induce bone regeneration. In addition, the attapulgite is also responsible for enriching preservation factors, and can also enhance the mechanical strength of calcium phosphate and regulate the degradation rate. BMSCs can differentiate toward bone tissue in the calcium phosphate environment and produce growth and nutrition factors related to bone formation.

[0027] The second object of the present invention is to provide a 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells prepared by the above method.

[0028] The third object of the present invention is to provide an application of the 3D printed bone defect repair scaffold prepared by the above method in the osteogenic differentiation of rBMSCs.

[0029] The fourth object of the present invention is to provide an application of the 3D printed bone defect repair scaffold prepared by the above method in the treatment of bone defects.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The present invention utilizes stereolithography (SLA) technology to prepare a 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells. This method has unique advantages: stereolithography is the earliest rapid prototyping manufacturing process with high maturity and has been tested over time. Its principle is the light-induced polymerization and cross-linking reaction of polymers; and it is directly made into a prototype from a CAD digital model, with a fast processing speed and a short product production cycle, without the need for cutting tools and molds; the method of the present invention can process prototypes and molds with complex structures and shapes or those that are difficult to form using traditional means according to requirements; and the method of the present invention can be operated online and remotely controlled, which is conducive to the automation of production.

[0032] (2) The porous scaffold structure prepared in the above step (1) of the present invention, especially the porous structure of the attapulgite / β-tricalcium phosphate bone scaffold material, not only affects the biological behaviors of bone marrow mesenchymal stem cells such as adhesion, migration and proliferation, but also stimulates BMSCs to secrete bone regeneration-related growth factors and adsorb them in the attapulgite, plays a loading and protective role, enhances the bone-inducing biological activity of the material, and accelerates bone formation. Therefore, the bone defect repair scaffold loaded with bone marrow mesenchymal stem cells prepared by the present invention has excellent physical, chemical and biological properties, and is expected to be used as a bone repair material with excellent biological properties in the biomedical field. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 is the X-ray diffraction pattern of the 3D printed bone defect repair scaffold in Example 1-5;

[0035] Figure 2is a scanning electron microscope image of the 3D printed bone defect repair scaffold in Example 1;

[0036] Figure 3 This is a live-dead staining picture of cells after the 3D printed bone defect repair scaffold and rBMSCs were co-cultured for 72 hours in Example 1;

[0037] Figure 4 This is a nuclear membrane staining picture of cells after the 3D printed bone defect repair scaffold and rBMSCs were co-cultured for 72 hours in Example 1;

[0038] Figure 5 This is a comparison of the expression of ALP, a gene related to osteogenic differentiation of rBMSCs, detected by real-time fluorescence quantitative PCR (qRTPCR) after co-culture of rBMSCs with β-TCP and β-TCP / ATT materials for 3, 7 and 10 days;

[0039] Figure 6 This is a comparison of the expression of OCN, a gene related to osteogenic differentiation of rBMSCs, detected by real-time fluorescence quantitative PCR (qRTPCR) after co-culture of rBMSCs with β-TCP and β-TCP / ATT materials for 3, 7 and 10 days;

[0040] in: Figure 5 , Figure 6 The vertical axis value of 1 represents the standard value. The picture is made after standardization with the control group. The value 1 means that the gene is not expressed and the material has no inducing effect. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.

[0042] According to the information contained in this application, various changes can be easily made to the precise description of the present invention for those skilled in the art.It should be understood that the scope of the present invention is not limited to defined processes, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention.

[0043] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0044] The average particle size of the β-tricalcium phosphate nanopowder involved in the following embodiments of the present invention is 51.43±14.25 nm. For the specific preparation method, please refer to Example 3 in patent CN 201910324645.3, a method for preparing nano-scale β-tricalcium phosphate.

[0045] The attapulgite involved in the following embodiments 6-10 of the present invention is specifically a micron-sized attapulgite spherical particle, the size of which is 15-30 μm, and the attapulgite is prepared by the following method: the purchased attapulgite raw material (purchased from Xuyi Botu Attapulgite Co., Ltd.) is spray granulated to obtain microspheres with uniform size and morphology. The feed rate and temperature during granulation are key factors affecting the shape and size of attapulgite particles, so the feed rate of spray granulation is maintained at 12 mL / min, and the process temperature should be controlled at 150 ° C. After spray granulation forms attapulgite particles with uniform particles and sizes that meet the requirements, the attapulgite spherical particles are calcined and degreased, and the heating method of the treatment is: slowly heating and controlling the final temperature to above 200 ° C and not more than 450 ° C, and keeping time 10-15h, so as to remove impurities, surface adsorbed water and pore water, solidify the particles, and improve the drug loading capacity of attapulgite.

[0046] The culture methods of rat bone mesenchymal stem cells (rBMSCs) involved in the following embodiments of the present invention are as follows: (1) Extraction of rBMSCs: Under sterile conditions, remove the femur from SD rats (weight 100-130g), expose the medullary cavity with bone forceps, and use a 1ml sterile syringe to draw H-DMEM basal culture medium containing 15% fetal bovine serum (FBS) and 1% penicillin-streptomycin to flush out the bone marrow in the bone until the bone is explanted. Then, blow the culture medium containing the bone marrow evenly, count and divide into culture bottles for culture.

[0047] (2) Cultivation and expansion of rBMSCs: rBMSCs were cultured in vitro and expanded to the required number: the cell culture flask was placed in an incubator at 37°C, 5% carbon dioxide and saturated humidity, and the medium was changed every 2 to 3 days. When the cells grew to 75-90% confluence, trypsin was used for digestion and passage. The present invention selected third-generation rBMSCs.

[0048] The third generation rBMSCs in good cell condition were selected, digested and collected by centrifugation, 100ul of culture medium was taken for dilution and 10ul was placed on a hemocytometer for counting, and the cell concentration was adjusted to obtain rBMSCs cell suspension.

[0049] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0050] Example 1

[0051] The preparation method of a 3D printed bone defect repair scaffold (porous β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment includes the following preparation steps:

[0052] Under light-proof conditions, 3.1368 g BYK-103 and 0.963 g TPO were weighed respectively, and then 3 ml TMPTA and 57 ml HDDA were added using a pipette, and the weighed prepolymer, photosensitive resin and dispersant were premixed on a magnetic stirrer for 30 min to obtain a mixed slurry;

[0053] Weigh 125.47 g of pre-dried β-tricalcium phosphate nanopowder and put it into a ball mill. At the same time, transfer the pre-mixed slurry into the ball mill and add zirconium oxide ball milling balls at a ball-to-material ratio of 2:1.

[0054] Weigh the ball mill jar, balance it in the ball mill and mix it at a speed of 300 rad / min for 6 h;

[0055] After ball milling, the ball milling beads were screened out, and after light-proof degassing treatment for 12 hours in a vacuum drying oven, a porous β-tricalcium phosphate scaffold was printed using an SLA 3D printer. The printed scaffold was cleaned with a cleaning agent, dried overnight, and then degreased and sintered under the following system: first, the temperature was kept at 450°C for 40 minutes, and then the temperature was increased to 1200°C at a heating rate of 2°C / min and kept for 2 hours;

[0056] The porous β-tricalcium phosphate scaffold after degreasing and sintering was disinfected and immersed in an rBMSCs cell concentration of 1*10 6 / ml of cell suspension, cultured in H-DMEM medium containing 10% FBS for 2 weeks, taken out, decellularized and freeze-dried to obtain a porous β-tricalcium phosphate scaffold.

[0057] Example 2

[0058] The preparation method of a 3D printed bone defect repair scaffold (porous β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment includes the following preparation steps:

[0059] Under light-proof conditions, 3.536 g BYK-103 and 0.858 g TPO were weighed respectively, and then 2.75 ml TMPTA and 52.25 ml HDDA were added using a pipette, and the weighed prepolymer, photosensitive resin and dispersant were premixed on a magnetic stirrer for 30 minutes to obtain a mixed slurry;

[0060] Weigh 141.44 g of pre-dried β-tricalcium phosphate nanopowder and put it into a ball mill. At the same time, transfer the pre-mixed slurry into the ball mill and add zirconium oxide ball milling balls at a ball-to-material ratio of 2:1.

[0061] Weigh the ball mill jar, balance it in the ball mill and mix it at a speed of 300 rad / min for 6 h;

[0062] After ball milling, the ball milling beads were screened out, and after light-proof degassing treatment for 12 hours in a vacuum drying oven, a porous β-tricalcium phosphate scaffold was printed using an SLA 3D printer. The printed scaffold was cleaned with a cleaning agent, dried overnight, and then degreased and sintered under the following system: first, the temperature was kept at 500°C for 30 minutes, and then the temperature was increased to 1250°C at a heating rate of 1.5°C / min and kept for 2 hours;

[0063] The porous β-tricalcium phosphate scaffold after degreasing and sintering was disinfected and immersed in an rBMSCs cell concentration of 1*10 6 / ml of cell suspension, cultured in H-DMEM medium containing 10% FBS for 2 weeks, taken out, decellularized and freeze-dried to obtain a porous β-tricalcium phosphate scaffold.

[0064] Example 3

[0065] The preparation method of a 3D printed bone defect repair scaffold (porous β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment includes the following preparation steps:

[0066] Under light-proof conditions, 1.4555 g BYK-103 and 0.486 g TPOL were weighed respectively, and 12 ml TMPTA and 18 ml HDDA were added using a pipette, and the weighed prepolymer, photosensitive resin and dispersant were premixed on a magnetic stirrer for 30 min to obtain a mixed slurry;

[0067] Weigh 58.22 g of pre-dried β-tricalcium phosphate nanopowder and put it into a ball mill. At the same time, transfer the pre-mixed slurry into the ball mill and add zirconium oxide ball milling balls at a ball-to-material ratio of 2:1.

[0068] Weigh the ball mill jar, balance it in the ball mill and mix it at a speed of 300 rad / min for 6 h;

[0069] After ball milling, the ball milling beads were screened out, and the porous β-tricalcium phosphate scaffold was printed using an SLA 3D printer after light-proof degassing treatment for 12 hours in a vacuum drying oven. The printed scaffold was cleaned with a cleaning agent, dried overnight, and then degreased and sintered under the following system: first, the temperature was kept at 460°C for 50 minutes, and then the temperature was increased to 1300°C at a heating rate of 2°C / min and kept for 100 minutes;

[0070] The porous β-tricalcium phosphate scaffold after degreasing and sintering was disinfected and immersed in an rBMSCs cell concentration of 1*10 6 / ml of cell suspension, cultured in H-DMEM medium containing 10% FBS for 2 weeks, taken out, decellularized and freeze-dried to obtain a porous β-tricalcium phosphate scaffold.

[0071] Example 4

[0072] The preparation method of a 3D printed bone defect repair scaffold (porous β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment includes the following preparation steps:

[0073] Under light-proof conditions, 1.4555 g BYK-103 and 0.486 g TPOL were weighed respectively, and then 18 ml TMPTA and 12 ml HDDA were added using a pipette, and the weighed prepolymer, photosensitive resin and dispersant were premixed on a magnetic stirrer for 30 min to obtain a mixed slurry;

[0074] Weigh 58.22 g of pre-dried β-tricalcium phosphate nanopowder and put it into a ball mill. At the same time, transfer the pre-mixed slurry into the ball mill and add zirconium oxide ball milling balls at a ball-to-material ratio of 2:1.

[0075] Weigh the ball mill jar, balance it in the ball mill and mix it at a speed of 300 rad / min for 6 h;

[0076] After ball milling, the ball milling beads were screened out, and after light-proof degassing treatment for 12 hours in a vacuum drying oven, a porous β-tricalcium phosphate scaffold was printed using an SLA 3D printer. The printed scaffold was cleaned with a cleaning agent, dried overnight, and then degreased and sintered under the following system: first, the temperature was kept at 485°C for 45 minutes, and then the temperature was increased to 1150°C at a heating rate of 0.5°C / min and kept for 150 minutes;

[0077] The porous β-tricalcium phosphate scaffold after degreasing and sintering was disinfected and immersed in an rBMSCs cell concentration of 1*10 6 / ml of cell suspension, cultured in H-DMEM medium containing 10% FBS for 2 weeks, taken out, decellularized and freeze-dried to obtain a porous β-tricalcium phosphate scaffold.

[0078] Example 5

[0079] The preparation method of a 3D printed bone defect repair scaffold (porous β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment includes the following preparation steps:

[0080] Under light-proof conditions, 1.6374 g BYK-103 and 0.4455 g TPOL were weighed respectively, and then 11 ml TMPTA and 16.5 ml HDDA were added using a pipette, and the weighed prepolymer, photosensitive resin and dispersant were premixed on a magnetic stirrer for 30 min to obtain a mixed slurry;

[0081] Weigh 65.4975 g of pre-dried β-tricalcium phosphate nanopowder and put it into a ball mill. At the same time, transfer the pre-mixed slurry into the ball mill and add zirconium oxide ball milling balls at a ball-to-material ratio of 2:1.

[0082] Weigh the ball mill jar, balance it in the ball mill and mix it at a speed of 300 rad / min for 6 h;

[0083] After ball milling, the ball milling beads were screened out, and after light-proof degassing treatment for 12 hours in a vacuum drying oven, a porous β-tricalcium phosphate scaffold was printed using an SLA 3D printer. The printed scaffold was cleaned with a cleaning agent, dried overnight, and then degreased and sintered under the following system: first, the temperature was kept at 400°C for 60 minutes, and then the temperature was increased to 1200°C at a heating rate of 2°C / min and kept for 2 hours;

[0084] The porous β-tricalcium phosphate scaffold after degreasing and sintering was disinfected and immersed in an rBMSCs cell concentration of 1*10 6 / ml of cell suspension, cultured in H-DMEM medium containing 10% FBS for 2 weeks, taken out, decellularized and freeze-dried to obtain a porous β-tricalcium phosphate scaffold.

[0085] Example 6

[0086] The preparation method of a 3D printed bone defect repair scaffold (attapulgite / β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment is basically the same as the preparation method in Example 1, with the only difference being that the mixed slurry in this embodiment also includes 1.24 g of attapulgite.

[0087] Example 7

[0088] The preparation method of a 3D printed bone defect repair scaffold (attapulgite / β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment is basically the same as the preparation method in Example 2, with the only difference being that the mixed slurry in this embodiment also includes 1.38 g of attapulgite.

[0089] Example 8

[0090] The preparation method of a 3D printed bone defect repair scaffold (attapulgite / β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment is basically the same as the preparation method in Example 3, with the only difference being that the mixed slurry in this embodiment also includes 0.61 g of attapulgite.

[0091] Example 9

[0092] The preparation method of a 3D printed bone defect repair scaffold (attapulgite / β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment is basically the same as the preparation method in Example 4, with the only difference being that the mixed slurry in this embodiment also includes 0.59 g of attapulgite.

[0093] Example 10

[0094] The preparation method of a 3D printed bone defect repair scaffold (attapulgite / β-tricalcium phosphate scaffold) loaded with bone marrow mesenchymal stem cells in this embodiment is basically the same as the preparation method in Example 4, with the only difference being that the mixed slurry in this embodiment also includes 0.66 g of attapulgite.

[0095] Comparative Example

[0096] The preparation method of a 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells in this comparative example comprises the following preparation steps:

[0097] Under light-proof conditions, 3.1368g BYK-103 and 0.963g TPO were weighed respectively, and then 3ml TMPTA and 57ml HDDA were added with a pipette, and the weighed prepolymer, photosensitive resin and dispersant were premixed on a magnetic stirrer for 30min to obtain a mixed slurry; after light-proof degassing treatment in a vacuum drying oven for 12h, a bone defect repair scaffold was printed using an SLA 3D printer, and the printed scaffold was cleaned with a cleaning agent, dried overnight, and then degreased and sintered under the following system; first, the temperature was kept at 450℃ for 40min, and then the temperature was increased to 1200℃ at a heating rate of 2℃ / min and kept for 2h;

[0098] The bone defect repair scaffold after degreasing and sintering was disinfected and immersed in an rBMSCs cell concentration of 1*10 6 / ml of cell suspension, cultured in H-DMEM medium containing 10% FBS for 2 weeks, then taken out, decellularized and freeze-dried to obtain a porous bone defect repair scaffold.

[0099] Figure 1 is the X-ray diffraction pattern of the 3D printed bone defect repair scaffold in Example 1-5, such as Figure 1As shown, the 3D printed bone defect repair scaffolds prepared in Examples 1-5 of the present invention have a single phase, high purity and crystallinity, and no other impurities.

[0100] Figure 2 is a scanning electron microscope image of the 3D printed bone defect repair scaffold in Example 1. Figure 2 As shown, the 3D printed bone defect repair scaffold prepared in Example 1 has a complete structure, uniform pore size, high porosity, provides structural support for tissues, and is beneficial to cell adhesion, proliferation, migration and differentiation, and the transportation of nutrients and metabolites.

[0101] Figure 3 This is a live-death staining picture of cells after 72 hours of co-culture of the 3D printed bone defect repair scaffold and rBMSCs in Example 1. Figure 3 It can be seen that the 3D printed bone defect repair scaffold prepared in Example 1 has excellent biocompatibility, high cell survival rate and good activity, indicating that the material has no cytotoxicity.

[0102] Figure 4 This is a nuclear membrane staining picture of cells after the 3D printed bone defect repair scaffold in Example 1 was co-cultured with rBMSCs for 72 hours. Figure 4 The cells shown are in good growth state, good spreading, and regular cell morphology, mostly in the shape of long spindles, indicating that the material has good biological activity and helps maintain the activity of stem cells.

[0103] The purity and crystallinity of the 3D printed bone defect repair scaffolds prepared in Examples 6-10 are also high, without other impurities. In addition, their structures are relatively complete, with uniform pore sizes and high porosity. The live and dead staining and nuclear membrane staining of the 3D printed bone defect repair scaffolds prepared in these Examples after co-culture with rBMSCs for 72 hours are similar to those in Figure 3 and Figure 4 The results are basically the same, indicating that the 3D printed bone defect repair scaffolds prepared in Examples 6-10 of the present invention also have excellent biocompatibility, high cell survival rate, and good activity, indicating that the material has no cytotoxicity.

[0104] Figure 5 The following is a comparison of the expression of ALP, a gene related to osteogenic differentiation of rBMSCs, detected by real-time fluorescence quantitative (qRTPCR) method after co-culturing rBMSCs with β-TCP and β-TCP / ATT materials for 3, 7 and 10 days in Example 1 and Example 6. The results show that the expression of the β-TCP / ATT material group at these three time points is higher than that of the β-TCP group, indicating that the introduction of ATT is more conducive to the osteogenic differentiation of BMSCs.

[0105] Figure 6The comparison chart is a comparison of the expression of OCN, a gene related to osteogenic differentiation of rBMSCs, detected by real-time fluorescence quantitative (qRTPCR) method after co-culturing rBMSCs with β-TCP and β-TCP / ATT materials for 3, 7 and 10 days in Example 1 and Example 6. The results show that the expression of OCN in the β-TCP / ATT material group was higher than that in the β-TCP group at these three time points, reaching a peak on the 7th day. This shows that the introduction of ATT is more conducive to the osteogenic differentiation of rBMSCs.

Claims

1. A method for preparing a 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells, characterized in that: The 3D printed bone defect repair scaffold has the functions of loading, protecting and slowly releasing bone regeneration-related factors secreted by BMSCs cells; the preparation method comprises the following steps: (1) Adding nano-β-tricalcium phosphate and micron-sized attapulgite to a pre-mixed photosensitive resin system according to a ratio, mixing the obtained mixed slurry, degassing it in a dark place, and then 3D printing and photocuring to obtain a porous scaffold, washing, drying, degreasing and sintering; the mass ratio of the nano-β-tricalcium phosphate and the micron-sized attapulgite is 95-105:1; the size of the micron-sized attapulgite is 15-30 μm; the solid content of the mixed slurry is 30 vol% to 40 vol%; the specific process of the degreasing and sintering is as follows: first, keep the temperature at 300-600°C for 30-60 minutes, then heat it to 1000-1500°C and keep it for 90-180 minutes; The micron-sized attapulgite is prepared by the following pretreatment method: spray granulation of the attapulgite raw material to obtain microspheres with uniform size and shape; the feed rate of the spray granulation is maintained at 12 mL / min, and the temperature of the process should be controlled at 150° C.; after the attapulgite particles with uniform particles and sizes meeting the requirements are formed by spray granulation, the spherical attapulgite particles are calcined and degreased, and the heating method of the treatment is: slowly heating and controlling the final temperature to be above 200° C. and not exceeding 450° C., and maintaining the temperature for 10-15 hours; (2) The porous scaffold after degreasing and sintering in step (1) is disinfected, and then a bone marrow mesenchymal stem cell suspension is inoculated on the porous scaffold at a certain concentration, cultured in H-DMEM medium containing 10% FBS for 1-2 weeks, and then taken out, decellularized and freeze-dried to obtain the 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells.

2. The method according to claim 1, characterized in that: The concentration of the bone marrow mesenchymal stem cell suspension in step (2) is 1-2×10 6 / ml.

3. A 3D printed bone defect repair scaffold loaded with bone marrow mesenchymal stem cells prepared by the method of claim 1 or 2.

Citation Information

Patent Citations

  • Method for preparing nanoscale beta-tricalcium phosphate

    CN110155972A

  • Calcium phosphate bone induction biological ceramic stent based on photocuring 3D printing technology and preparation method thereof

    CN109650909A

  • Mesenchymal stem cell epimatrix-loaded 3D printing bone defect repair scaffold and preparation method thereof

    CN114887116A